2017
DOI: 10.1080/14780887.2017.1359352
|View full text |Cite
|
Sign up to set email alerts
|

“Beyond words”: a researcher’s guide to using photo elicitation in psychology

Abstract: Do w nlo a d e d fro m: h t t p://i n si g h t. c u m b ri a. a c. u k/i d/ e p ri n t/ 3 0 8 1/ U s a g e o f a n y i t e m s f r o m t h e U n i v e r s i t y o f C u m b r i a' s i n s t i t u t i o n a l r e p o s i t o r y 'I n s i g h t' m u s t c o n f o r m t o t h e f o l l o w i n g f a i r u s a g e g u i d e l i n e s .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
102
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 62 publications
1
102
0
10
Order By: Relevance
“…This study utilized a combination of photo‐elicitation (Collier, ) and IPA (Smith, ). Photo‐elicitation promotes the use of photographs within an interview setting to better understand the experiences of participants (Bates, McCann, Kaye, & Taylor, ). Our aim was to empower people with lived experience of hoarding to photograph personal possessions that felt linked to their sense of self or to the identity of others for discussion in one‐to‐one interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study utilized a combination of photo‐elicitation (Collier, ) and IPA (Smith, ). Photo‐elicitation promotes the use of photographs within an interview setting to better understand the experiences of participants (Bates, McCann, Kaye, & Taylor, ). Our aim was to empower people with lived experience of hoarding to photograph personal possessions that felt linked to their sense of self or to the identity of others for discussion in one‐to‐one interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Our aim was to empower people with lived experience of hoarding to photograph personal possessions that felt linked to their sense of self or to the identity of others for discussion in one‐to‐one interviews. Researchers have suggested that photography often helps participants reflect more deeply on their lived experience (Bates et al ., ; Del Busso, ) and develop self‐awareness (Teti, Kabel, French, & Farnan, ; Werremeyer, Skoy, & Aalgaard Kelly, ). Thus, we hoped the use of photography would assist both us and the participants to further understand the granularity surrounding their emotional attachments to possessions.…”
Section: Methodsmentioning
confidence: 99%
“…En estas situaciones de narración visual, la integración de ambas aproximaciones mediante procesos de discusión, proporciona la emergencia de una comprensión del contenido narrado y, de forma especial, del sistema de valores, creencias y referentes interpretativos del creador de la fotografía que son objeto de debate. Una estructura que se ha venido utilizando en otros campos profesionales como la terapia, la evaluación y el diagnóstico (Bates, McCann, Kaye, & Taylor, 2017;Buchanan, 1998;Diamon, 1996;Kearns, 2012;Salmon, 2001), y que en las últimas décadas ha emergido con fuerza en los campos de la sociología y la antropología para la comprensión de las formas de vida de diferentes grupos y colectivos sociales (Copes, Tchoula, Brookman, & Ragland, 2018;Pauwels, 2020;Sestito et al, 2017).…”
Section: La Foto-elicitación En La Formación Del Profesoradounclassified
“…Destaca-se que além do consentimento verbal sobre a realização da entrevista, a pesquisadora obteve o consentimento verbal adicional durante a gravação de áudio, para reiterar a utilização das fotos tanto como uma ferramenta auxiliar na coleta de dados, quanto na própria tese e possíveis publicações futuras (Bates, McCann, Kaye, & Taylor, 2017).…”
Section: Construção Do Corpus Da Pesquisaunclassified
“…Motivações semelhantes levou a pesquisadora a utilizar a foto-elicitação, especialmente quando combinadas com as vantagens descritas no decorrer desta seção (Bates, McCann, Kaye, Taylor, 2017).…”
Section: Construção Do Corpus Da Pesquisaunclassified